Developing an Edutainment-Based Probing-Prompting Learning Model for Teaching Civic Education Subject to Fifth Graders - Abbas, Atip Nu rharini, Nuraeni (Universitas Negeri Semarang, 2017)
This study was conducted based on the problem found in the teaching and learning process of civic education subject that has not used various learning model yet. In fact, this phenomenon caused the low achievement of students in this subject. Further, this study was intended to develop an edutainment-based probing-prompting learning model for teaching civic education subject. For more, the research and development design was employed to purse this objective. Meanwhile, the data collection techniques used were questionnaire, observation, interview, tests, and documentation. Accordingly, the result showed that: (1) the learning model was developed regarding learning model components as well as teachers and students' needs; (2) the material experts gave 85% score (feasible), while the experts of learning model gave 81.25% score (feasible); (3) there found cognitive learning achievement average with t-test value as many as -6.298 and also improvement of 0.48 with fair criterion. The developed model also gave effective result on the affective and psychomotor learning achievement with the averages of 88.49 and 91.27. Therefore, this study concludes that the edutainment-based probing-prompting learning model is feasible and effective for teaching civic education subject. Also, this study suggests that this product is used by teachers to improve students' learning achievement.